Deployment of stationary and dynamic charging infrastructure for electric vehicles along traffic corridors. (April 2017) - Chen, Zhibin; Liu, Wei; Yin, Yafeng
Highlights: Charging facility (stations or lanes) choice equilibrium is modeled. Optimal deployment plans of charging stations and lanes under either public or private provision are explored. The charging lanes are competitive as compared with charging stations for attracting drivers. In the private provision scenario, operating charging lanes is more profitable than operating charging stations. Abstract: As charging-while-driving (CWD) technology advances, charging lanes can be deployed in the near future to charge electric vehicles (EVs) while in motion. Since charging lanes will be costly to deploy, this paper investigates the deployment of two types of charging facilities, namely charging lanes and charging stations, along a long traffic corridor to explore the competitiveness of charging lanes. Given the charging infrastructure supply, i.e., the number of charging stations, the number of chargers installed at each station, the length of charging lanes, and the charging prices at charging stations and lanes, we analyze the charging-facility-choice equilibrium of EVs. We then discuss the optimal deployment of charging infrastructure considering either the public or private provision. In the former, a government agency builds and operates both charging lanes and stations to minimize social cost, while in the latter, charging lanes and stations are assumed to be built and operated by two competing private companies to maximize their own profits. Numerical experiments based on currently available empirical data suggest that charging lanes are competitive in both cases for attracting drivers and generating revenue.